2021
DOI: 10.1111/jfpe.13834
|View full text |Cite|
|
Sign up to set email alerts
|

Retracted: Different effects of continuous and intermittent alternative magnetic field on inhibiting chilling injury of bananas

Abstract: Chilling injury (CI) is one of the important factors to reduce tropical fruit preservation quality. A low‐temperature electromagnetic preservation system is developed by combining the refrigerated storage technology and electromagnetic biological effect to decrease the CI damage. Based on this system, the experimental study and mechanism analysis of alternating magnetic field inhibiting the CI of bananas are carried out. Experimental results show that compared with the control group (CK), the alternative magne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 39 publications
(46 reference statements)
0
3
0
Order By: Relevance
“… Jia et al (2015) also reported that the firmness of cantaloupe melons increased after magnetic field treatment. During fruit softening of peach and banana, it had been observed obvious depolymerization of cell wall components which led to the disruption of cell wall structure and eventually the decline of fruit firmness ( Zhao et al, 2021 , Zhao et al, 2021 , Shinga and Fawole, 2023 ). As with TSS, it was always lower in 3 mT + 4 °C group than those of other two groups while TA content was maintained by combined treatment during the whole storage ( Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… Jia et al (2015) also reported that the firmness of cantaloupe melons increased after magnetic field treatment. During fruit softening of peach and banana, it had been observed obvious depolymerization of cell wall components which led to the disruption of cell wall structure and eventually the decline of fruit firmness ( Zhao et al, 2021 , Zhao et al, 2021 , Shinga and Fawole, 2023 ). As with TSS, it was always lower in 3 mT + 4 °C group than those of other two groups while TA content was maintained by combined treatment during the whole storage ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“… Lv et al (2022) found that magnetic field (2 mT, 50 Hz) could maintain better color and firmness of fresh-cut apples during 9 d storage at 4 °C. It was also reported that polyphenol oxidase activity and MDA accumulation of bananas under magnetic field treatment (2 mT, 60 Hz) were lower during 10 d storage ( Zhao et al, 2021 , Zhao et al, 2021 ). Liu et al (2023) discovered that magnetic field (4 mT, 50 Hz) retard the senescence and decay of harvested strawberries by maintaining energy state and regulating respiratory metabolism.…”
Section: Introductionmentioning
confidence: 86%
“…16 It can also affect related biochemical processes by changing the structure of enzymes. 17 The application of a magnetic eld is also benecial to reduce the chilling injury of fruits and vegetables. 18 In recent years, people have conducted extensive research on the role of a magnetic eld and found that an electromagnetic eld has the effect of sterilization and can delay the aging and spoiling of a State Key Laboratory of Food Science and Technology, Jiangnan University, 214122 Wuxi, Jiangsu, China.…”
Section: Introductionmentioning
confidence: 99%